OIL SLUDGE AND TAR SANDS AS AN IMPORTANT SOURCE OIL AND PROBLEMATIC ENVIRONMENTAL FACTORS - V. F. Khairutdinov; F. M. Gumerov (Известия высших учебных заведений: Проблемы энергетики)
The paper represents the results of implementation of liquid and supercritical fluid extraction processes in order to extract oil-products from oil sludge. A mixture consisting of propane (75 wt%) and butane (25 wt%) has been applied as the extractant. Initial oil sludge is characterized by the absence of water and content of solids in an amount of 12.05% by weight. The extraction processes have been conducted in a temperature range of85-160°C and pressure range of 5-50 MPa.